2011
DOI: 10.1371/journal.ppat.1002421
|View full text |Cite
|
Sign up to set email alerts
|

Wall Teichoic Acids of Staphylococcus aureus Limit Recognition by the Drosophila Peptidoglycan Recognition Protein-SA to Promote Pathogenicity

Abstract: The cell wall of Gram-positive bacteria is a complex network of surface proteins, capsular polysaccharides and wall teichoic acids (WTA) covalently linked to Peptidoglycan (PG). The absence of WTA has been associated with a reduced pathogenicity of Staphylococcus aureus (S. aureus). Here, we assessed whether this was due to increased detection of PG, an important target of innate immune receptors. Antibiotic-mediated or genetic inhibition of WTA production in S. aureus led to increased binding of the non-lytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 49 publications
1
52
1
Order By: Relevance
“…Therefore, crq ko flies are susceptible to Gram-positive bacteria and fungal infections and strongly susceptible to infection with S . aureus , a bacterium specifically cleared by phagocytosis [19,62,63]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, crq ko flies are susceptible to Gram-positive bacteria and fungal infections and strongly susceptible to infection with S . aureus , a bacterium specifically cleared by phagocytosis [19,62,63]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, changes in PG composition and altered PG synthase activity contribute to bile resistance in Salmonella enterica (39,41) and PG composition changes during stationary phase (42). Pathogenic bacteria can also remodel PG to avoid a host response (5,(43)(44)(45)(46). Previous studies have shown that the number and activity of PG synthetic enzymes and their interaction partners vary significantly in different organisms (47).…”
Section: Discussionmentioning
confidence: 99%
“…Lysosome can kill bacteria through cell wall degradation, which further generates peptidoglycan (PPG) fragments that can be recognized by pattern-recognition receptors (PRRs, see sidebar) such as NOD2 (35) and peptidoglycan recognition protein (25). Gram-positive pathogens have evolved mechanisms to PPG less recognizable to lysozyme, including PPG modification in SPN (122) and GAS (41), O -acetylation in SPN (32) and S. aureus (11), and masking of PPG with covalently linked wall teichoic acid (WTA) structures in S. aureus (8). Functionally, modification of PPG to impart lysozyme resistance results in not only evasion of detection by PRRs, but also limiting of host production of important inflammatory mediators such as interleukin (IL)-1β via the Nod-like receptor (NLR) family pyrin-domain-containing 3 (NLRP3) inflammasome (see sidebar) and interferon-β (64, 109).…”
Section: Resistance To Phagocytic Granule Componentsmentioning
confidence: 99%